Perbandingan Pengujian Pengeringan Gula Semut dengan Kapasitas 84 Kg dan 120 Kg - MULIADI, Ade ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Along with the prapid advancement of tecnologi then life is accompanied by innovations of processes outomatisasi, compelling reasons which prompted the formation of the dryer this sugar, beginning from constrained the process of warming experienced by growers of sugar. The working of the dryer on the dryer the sugar is to use the heater which is controlled by the thermo controller which is then determined by the timer, during the specified period and also the temperature that has been desired ocurrence of harm aimed at farmers sugar caused by weather and season. For that surveyors laid out the dryer the sugar but aims to anticipate the occurrence of freezing on the sugar ant is not the heated due to weather these machines also speed the process of warming initially heated by solar power using time 1-2 days, here a dryer speeds up the drying process by about 4-8 hours so with the dryer the sugar are ants sugar farmers will be faster and easier to do the drying process